2019
DOI: 10.1021/acs.jpca.8b09642
|View full text |Cite
|
Sign up to set email alerts
|

Excited-State Vibrational Frequencies: Restricted Virtual Space Time-Dependent Density Functional Theory

Abstract: Calculating accurate vibrational frequencies for molecules with electronically excited states has an important function in many areas of photochemistry. However, calculations are often limited to smaller molecules due to the rapid growth in the degrees of freedom that must be taken into account to accurately describe larger systems. The applicability of the restricted virtual space (RVS) approximation has been studied within adiabatic linear response time-dependent density functional theory when calculating ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…As the excitation energy is tuned beyond the core-ionization threshold, the scattering cross-section is overtaken by the non-resonant emission process. Furthermore, restricting the virtual space in TD-DFT has been proposed early on as a means for tackling states for adsorbed molecules as well as molecules in solution, [41][42][43] and it has been shown to also be a suitable route to obtaining excited states energies, 29 geometries 44 and vibrational frequencies 45 of large systems. Virtual space restriction has also been successfully used in RIXS simulations at the L-edge of transition metal complexes within the multi-configurational Kohn-Sham ROCIS method.…”
Section: General Theory Of Resonant Inelastic X-ray Scatteringmentioning
confidence: 99%
“…As the excitation energy is tuned beyond the core-ionization threshold, the scattering cross-section is overtaken by the non-resonant emission process. Furthermore, restricting the virtual space in TD-DFT has been proposed early on as a means for tackling states for adsorbed molecules as well as molecules in solution, [41][42][43] and it has been shown to also be a suitable route to obtaining excited states energies, 29 geometries 44 and vibrational frequencies 45 of large systems. Virtual space restriction has also been successfully used in RIXS simulations at the L-edge of transition metal complexes within the multi-configurational Kohn-Sham ROCIS method.…”
Section: General Theory Of Resonant Inelastic X-ray Scatteringmentioning
confidence: 99%
“…Even greater reductions in the computational complexity may also be possible through the development of colocalization procedures that localize both the normal mode and molecular orbital spaces at the same time to achieve an optimal balance of coordinates. A recent study has suggested that a similar combination of orbital and normal mode localizations could show potential for improving the efficiency of calculating vibrational frequencies for electronically excited states when using the restricted virtual space approximation to time-dependent DFT (RVS-TDDFT) . However, this is considered to be outside the scope of the current investigation.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study has suggested that a similar combination of orbital and normal mode localizations could show potential for improving the efficiency of calculating vibrational frequencies for electronically excited states when using the restricted virtual space approximation to time-dependent DFT (RVS-TDDFT). 93 However, this is considered to be outside the scope of the current investigation. Similarly, given the potential that two-electron attenuation has to improve efficiency in the calculation of vibrational properties, future investigations may also be warranted into the distance decay behavior of the correlated two-electron terms in attenuated MP2 theory.…”
Section: ■ Computational Detailsmentioning
confidence: 96%
“…Experimental observations and theoretical models can be linked by accurately matching theoretically predicted and observed properties. The development of theoretical methods to efficiently and accurately predict these properties and the assessment of these methods is therefore an area of ongoing research, and molecular vibrational simulations have even recently been performed using blockchain computers. , …”
Section: Introductionmentioning
confidence: 99%